When fears of exclusion meet fears of engulfment: how hybrid medical co-directors modulate role distance - Emilie Gibeau (Leadership in Health Services, 2026)
Purpose Hybrids are professionals who simultaneously hold roles spanning two organizational domains, such as physician-managers, who combine a clinical and a managerial appointment. They embody and bridge otherwise separated groups, a position often imbued with tensions. To manage this tension, hybrids constantly modulate closeness and distance. This study aims to explore how hybrid physician-managers in senior co-leadership roles manage their distance from the management and medical components of their role. Design/mAethodology/approach Relying on the narratives of 20 physician managers from four healthcare organizations located in Quebec, I identified 13 practices that these hybrids used to shape role distance, with a noteworthy subset of four practices specifically affecting distance from the administrative co-director. Findings This study revealed hybrids investing significantly in constructing vertical distance between their role and others, casting or assigning others to roles and leveraging their co-leadership relationship to modulate distance and proximity. Distance was modulated through rather gentle, narrow and privately demeaning practices rather than grand gestures. Practices consistently contributed to creating another space – a state of “elsewhereness” different from one’s physical place – where hybrids could shine. Originality/value This study contributes originality by applying the lens of role distancing to hybrid physician-managers in senior co-leadership roles, revealing how they actively negotiate proximity and distance between medicine and management. Although hybrids’ fears of ostracism by medicine and co-optation by management are well-documented, this study uncovers some hybrids’ fear of being engulfed by the medical component of their role.